Systemically Silencing Long Non-coding RNAs Maclpil With Short Interfering RNA Nanoparticles Alleviates Experimental Ischemic Stroke by Promoting Macrophage Apoptosis and Anti-inflammatory Activation - Wang, Yan; Liu, Cuiying; Chen, Yong; Chen, Tiffany; Han, Tao; Xue, Lixiang; Xu, Baohui (Frontiers in Cardiovascular Medicine, 2022)
Background Maclpil is a proinflammatory long non-coding RNA highly expressed on monocyte-derived macrophages in the ischemic brain. This study investigated the impact and the mechanisms of systemically delivering nanoparticle Maclpil short interfering RNA (siRNA) on experimental ischemic stroke in a mouse model. Methods Ischemic stroke (focal cerebral ischemia) was induced in male C57BL/6 mice through the middle cerebral artery occlusion. Three hours thereafter, mice were intravenously injected with Maclpil siRNA or scramble siRNA nanoparticles. Bone marrow cell-derived macrophages were transfected with Maclpil or scramble siRNA and subjected to oxygen glucose deprivation culture. The influence of silencing Maclpil on stroke outcomes, neuroinflammation, and macrophage fates was assessed via histology, flow cytometry, Western blotting, and quantitative PCR analysis. Results Three days following stroke induction, siRNA silencing Maclpil substantially reduced ischemic infarction size and improved neurological behaviors. Silencing Maclpil also markedly attenuated the accumulation of monocyte-derived macrophages, CD4+ T cells, and CD8+ T cells in the ischemic hemisphere without affecting microglia cellularity. Reciprocally, myeloid cells and both subsets of T cells were elevated in mouse peripheral blood following Maclpil siRNA treatment. Under oxygen glucose deprivation conditions that mimicked hypoxia and hypoglycemia in vitro, Maclpil siRNA silencing augmented macrophage apoptosis in conjunction with upregulation of proapoptotic Bax and caspase 3 expressions. siRNA knocking down Maclpil skewed macrophages from proinflammatory classical toward anti-inflammatory alternative activation as evidenced by increased arginase 1, Ym1, and Fizz1 and reduced inducible nitric oxide synthase, IL-1β, and TNF-α mRNA levels. Consistent with macrophage phenotype switching, silencing Maclpil by siRNA enhanced fatty acid oxidation as indicated by increased mRNA levels of 3 key metabolic enzymes (ACADM, ACADVL, and HADHA). Conclusion Systemically silencing Maclpil by siRNA nanoparticles attenuated experimental ischemic stroke by promoting macrophage apoptosis and anti-inflammatory alternative activation. Identifying and targeting Maclpil human homolog(s) may help develop a novel therapy for stroke clinical management.